PENERAPAN MEDIA PUZZLE UNTUK MENUMBUHKAN HASIL BELAJAR MATEMATIKA DAN KETERAMPILAN MOTORIK HALUS SISWA KELAS II SD NEGERI KEMUKTEN 02 - Wildan Baghiz Naufal; Diah Sunarsih; Atikah Mumpuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics is often considered a difficult and boring subject, especially among elementary school students. This study aims to examine the effectiveness of puzzle media in improving mathematics learning outcomes and fine motor skills of second-grade students at SD Negeri Kemukten 02. The research employed a quantitative approach with a one-group pretest-posttest design. A total of 22 students were selected purposively as research subjects. Data were collected through mathematics tests and observation sheets for fine motor skills. The results showed a significant increase in students' learning outcomes, with the average pretest score rising from 62.73 to 82.18 after the implementation of puzzle media. The paired sample t-test revealed a significance value of 0.000, indicating a statistically significant difference. In addition, students demonstrated notable improvements in fine motor indicators such as hand-eye coordination, object arrangement, and task persistence. The use of puzzle media created a more active and engaging learning environment, enabling students to understand abstract mathematical concepts in a more concrete and enjoyable way. These findings suggest that puzzle media is an effective alternative to enhance both cognitive and psychomotor aspects in early mathematics education.